PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PT LIMAS PRIMA STEEL KOTA TANGERANG - Dedek Kumara; Iip Marlia (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study was to determine the effect of product quality and service quality on purchasing decisions at PT. Limaz Prima Steel Tangerang, either partially or simultaneously. The method used is the associative method. The sampling technique used was random sampling using a sample of 85 respondents. Data analysis used validity test, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are Product Quality has a significant effect on Customer Satisfaction with the regression equation Y = 14.207 + 0.380X1, a correlation value of 0.630 means that the two variables have a strong level of relationship with a determination coefficient of 39.7%. Hypothesis test obtained t count> t table or (7,398> 1,989). Thus H0 is rejected and H1 is accepted, meaning that there is a significant influence between Product Quality and Customer Satisfaction. Service Quality has a significant effect on Customer Satisfaction with the regression equation Y = 9,531 + 0.652 X 2, the correlation value is 0.702, meaning that both have a strong relationship level with a determination coefficient of 49.2%. Hypothesis test obtained t count> t table or (8.974> 1.989). Thus H0 is rejected and H2 is accepted, meaning that there is a significant influence between Service Quality and Customer Satisfaction. Product Quality and Service Quality have a significant effect on Customer Satisfaction with the regression equation Y = 6.875 + 0.180X1 + 0.470X2. The correlation value of 0.737 means that the independent variable and the dependent variable have a strong level of relationship with a determination coefficient of 53.4% while the remaining 46.6% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (48,741> 2,720). Thus H0 is rejected and H3 is accepted. This means that there is a significant influence simultaneously between Product Quality and Service Quality on Customer Satisfaction at PT. Limaz Prima Steel Tangerang